Arecaceae Diversity In Sambik Bangkol Village, North Lombok Regency, Indonesia - Slamet Mardiyanto Rahayu; Syuhriatin (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
This research investigates the diversity of Arecaceae (palm) species in Sambik Bangkol Village, North Lombok Regency. The research was carried out using observation methods on the landscape of Sambik Bangkol Village. Species identification and individual counting were carried out. Then an analysis of the Shannon-Wiener species diversity index was carried out. A field survey in Sambik Bangkol Village identified fifteen distinct species, namely: Areca catechu, Arenga pinnata, Calamus manan, Caryota mitis, Cocos nucifera, Corypha utan, Cyrtostachys renda, Dypsis lutescens, Hyophorbe lagenicaulis, Licuala grandis, Phoenix dactylifera, Rhapis excelsa, Roystonea regia, Salacca zalacca, and Wodyetia bifurcata. Data analysis yielded a diversity index of 1.77, placing the area’s palm diversity in the moderate category. Moderate species diversity reflects the stability and resilience of the community, with each species playing an important role in maintaining overall ecosystem function. This allows the ecosystem to remain productive and able to adapt to small changes without experiencing significant disruption.